Pitch perfect 2 [videorecording (DVD)] - Banks, Elizabeth, 1974-; Kendrick, Anna; Wilson, Rebel; Steinfeld, Hailee; Snow, Brittany, 1986- (Universal Studios Canada, 2015)
The Barden Bellas are back to pitch slap the world. It's been three years since the Bellas brought their signature vocals, style and attitude to become the first all-female group to win a national title. But when they get banned after a scandal that threatens to derail their last year at Barden, the three-time defending champs worry that this time they've lost their harmony for good. The Bellas must fight for their right to win the World Championships of A Cappella in Copenhagen.